Estudo de materiais supercondutores em forma de SQUID com uma constrição usando métodos de paralelização computacional - Severino, André Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
It is remarkable the current development of science and technology related to superconducting materials. Examples of using this type of material, such as storage of energy as supercurrents, the Maglev-type trains, which also provides use of supercurrents generating high values of magnetic field that can provide levitation and propulsion. Aplications of this nature, among others, require a deep understanding of the bahavior of the fundamental physical properties of superconductors, both from the macroscopic and microscopic point of view. As one example, the formation of vortex lattice in superconducting materials in the presence of applied magnetic fields and/or transport chains whose magnitudes when they exceed certain critical values allow the quantized magnetic flux entrance. With respect to the methods used in this work, we studied the behavior and characteristics of a material with mesoscopic dimensions in a geometry of a superconducting quantum interference device - SQUID. Such device is a kind of very sensitive magnetometer, able to perform very faint magnetic fields measures - using a computer simulation algorithm. The simulation basically acts to apply magnetic fields at certain time steps - with fixed temperature - to the modeled material, allowing the study of the characteristics of this type of material by means of output data generated by the simulator, which allows the construction of graphs to study the order parameter behavior, current densities, vortex formation, and other related parameters. Thus, we review the phenomenological theories and developed a numerical solution algorithm of the involved equations, which have no exact solution. Then we use the CUDA technology with the C language to implement this algorithm and apply it to solving the problem of a SQUID with a small construction. Finally, the graphics are constructed using the data generated by the simulator for analysis and interprettion of the behavior of the...

É notável o desenvolvimento atual da Ciência e Tecnologia relacionada aos materiais supercondutores. Exemplos de utilização deste tipo de material, são o armazenamento de energia em forma de supercondutores, trens do tipo Maglev, cujo uso das supercorrentes também proporciona a geração de altos valores de campos magnético que podem proporcionar levitação e propulsão. Aplicações desta natureza, dentre outras, requerem uma profunda compreensão do comportamento das propriedades físicas fundamentais dos supercondutores, tnato do ponto de vista macroscópico. Como exemplo, podemos citar a formação de rede de vórtices em materiais supercondutores na presença de campos magnéticos aplicados e/ou de correntes de transporte, cujas magnitudes, quando ultrapassam determinados valores críticos, permitem a entrada quantizada de fluxo magnético. Com relação aos métodos utilizados neste trabalho, estudamos o comportamento e as características de um material de dimensões mesoscópicas em formato de dispositivo supercondutor de interferência quântica - SQUID, um tipo de magnetômetro muito sensível, capaz de realizar medidas de campos magnéticos muito tênues - usando um algoritmo de simulação computacional. A simulação basicamente atua no sentido de se aplicar campos magnéticos em passos d tempo determinados - a temperatura fixa - ao material modelado, o que permite o estudo das características deste tipo de material por meio dos dados de saída gerados pelos simulador, os quais permitem a construção de gráficos para estudo do comportamento do parâmetro de ordem, densidades de corrente, formação de vórtices, entre outros parâmetros relacionados. Assim, fazems uma revisão das teorias fenomenológicas e desenvolvemos uma algorítimo de solução numérica das equações envolvidas, as quais não possuem solução exata. Em seguida usamos a tecnologia CUDA com a linguagem C para implementar este algoritmo e...
Keywords: Supercondutividade; Movimento turbulento; Magnetometro; Simulação (Computadores); Superconductivity